2019
DOI: 10.1002/jhet.3527
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of NewS‐Glycosides andN‐Glycosides of Pyridine‐biphenyl System with Antiviral Activity and Induction of Apoptosis inMCF7 Cells

Abstract: Glycosylation of small molecule‐based drugs can dramatically improve the biological activities of the parent scaffold. In the current study, S‐glycosides and N‐glycosides of polyfunctionalized pyridine‐biphenyl system tethered with benzotriazole moiety were designed and synthesized. S‐Glycosides of pyridine‐2‐thione derivatives 5a–h and N‐glycosides of pyridine‐2‐one derivatives 9a,b were synthesized by a facile, convenient, and high‐yielding procedure. The epimers glucose and galactose, acetylated or deacetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Glycosides are secondary metabolites that widely exist in all organs of plants, such as flowers, fruits, leaves, skins, and roots, etc ( Gruner et al, 2002 ), and previous studies found that glycosides had a wide range of pharmacological activities, such as antiviral ( Chen W. et al, 2019 ; Khodair et al, 2019 ), antibacterial ( Mohammed et al, 2019 ), anticancer ( Gurung et al, 2018 ; Rahim et al, 2020 ), antioxidant ( Jiang et al, 2018 ; Hawas et al, 2019 ), and anti-HIV ( He et al, 2019 ) activities. Meanwhile, studies also found that glycoside derivatives showed exceeding inhibitory activities against plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosides are secondary metabolites that widely exist in all organs of plants, such as flowers, fruits, leaves, skins, and roots, etc ( Gruner et al, 2002 ), and previous studies found that glycosides had a wide range of pharmacological activities, such as antiviral ( Chen W. et al, 2019 ; Khodair et al, 2019 ), antibacterial ( Mohammed et al, 2019 ), anticancer ( Gurung et al, 2018 ; Rahim et al, 2020 ), antioxidant ( Jiang et al, 2018 ; Hawas et al, 2019 ), and anti-HIV ( He et al, 2019 ) activities. Meanwhile, studies also found that glycoside derivatives showed exceeding inhibitory activities against plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial for cancer cells to maintain their uncontrollable proliferation. Therefore, triggering apoptosis is a main mode of action for most of the anti-cancer agents [16,17,19,[42][43][44][45]. In the present study, A. machrostachyum extract reduces EST size through induction of apoptosis as evidenced histologically (presence of apoptotic cells), and molecularly (up-regulation of the apoptotic genes p53, Bax, and caspase 3, and downregulation of the antiapoptotic gene Bcl2 as well as increase DNA damage).…”
Section: Discussionmentioning
confidence: 51%
“…Rapid Overlay Chemical Similarity (ROCS) study was operated to explain the similarity of the compounds and to figure out the most important pharmacophoric features. Glycosides of structurally similar heterocyclic systems have been reported before [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%